A comparative study on crystallization behavior, phase stability, and binding energy in pure and Cr-doped TiO2 nanotubes - Low, It Meng; Albetran, Hani; Prida, V.; Vega, V.; Manurung, P.; Ionescu, M. (Cambridge University Press, 2013)
Use of nanostructured TiO2 for photocatalysis is a cost-effective and sustainable technology. However, to make this an attractive viable technology will require the design of TiO2 photocatalyst capable of harnessing the energy of visible light. One possible solution is the doping of TiO2 to reduce its band gap. In this paper, the effect of Cr-doping by ion implantation on the in situ crystallization and phase stability of anodic TiO2 nanotubes at elevated temperature is described. Cr-doping has dramatically reduced the fraction of anatase-to-rutile transformation and lowered the crystallization temperature of anatase from 600 to 400 °C and rutile from 600 to 500 °C. Ion beam analysis by Rutherford backscattering spectrometry has confirmed the existence of Cr ions composition gradation in doped TiO2 nanotubes. The real doping of Ti lattices with Cr ions was evidenced by the analyses of surface compositions and chemical states of the nanotubes using x-ray photoelectron spectroscopy.